A new approach: Laparoscopic right hemicolectomy with priority access to small bowel mesentery - Pi, Feng; Peng, Xudong; Xie, Chaozheng; Tang, Gang; Qiu, Yuhao; Chen, Zhenzhou; Wei, Zhengqiang (Frontiers in Surgery, 2023)
Background: For laparoscopic right hemicolectomy, the intermediate approach is commonly employed. However, it possesses several disadvantages. In this study, we compare two surgical approaches, preferential access to the small bowel mesentery and the traditional intermediate approach. Methods: The clinical data of 196 patients admitted to the First Hospital of Chongqing Medical University for laparoscopic right hemicolectomy from January 2019 to January 2022 were retrospectively collected and divided into the small bowel mesenteric preferential and traditional intermediate access groups. The operative time, intraoperative bleeding, number of lymph node dissection, postoperative anal venting time, toleration of solid and liquid intake, and postoperative hospital stay and complications were compared between the two different approaches. Results: 81 cases of small bowel mesenteric preferential access and 115 cases of intermediate approach for right hemi-colonic radical resection were compared. The operative time was 191.98±46.05 min and 209.48±46.08 min in the small bowel mesenteric preferential and intermediate access groups, respectively, and the difference was statistically significant. There were no significant differences in the intraoperative bleeding and lymph node clearance. However, the scatter plot analysis showed that the number of severe intraoperative bleeding was relatively less in the small mesenteric preferential access group when compared to the intermediate approach group. Additionally, there were no statistically significant differences in the first exhaust and defecation times, hospital stay after operation, toleration of solid and liquid intake, and postoperative complication between the two groups. Conclusions: In laparoscopic right hemicolectomy, the small bowel mesenteric preference approach can significantly shorten the operation time compared with the intermediate approach. It can also reduce intraoperative bleeding and the operation is simple and safe to perform, making it suitable for inexperienced surgeons. Therefore, the small bowel mesenteric preferential approach has the potential to be a suitable alternative and deserves further clinical promotion and application.